Internationalisation expectations of entry - level and senior university students - a Malaysian perspective - De Jager, J.; Soontiens, Werner (University of Florida, 2008)
A more competitive and commercialised educational environment has contributed to not only the introduction of service quality measurement at higher education institutions but also an increased notion to internationalise. While traditionally institutions assume that students have relatively homogeneous expectations over time this approach is questioned, particularly when students study across national and cultural borders. It is argued that entry level students are required to adapt to academic and service systems and standards while senior students have a better and more realistic understanding of the actual environment. Ultimately this exposure impacts on student interpretations of the international position and standing of institutions. The aim of this paper is to investigate the expectations of entry level and senior students in respect of international image and academic related issues. The data represents these two student groups in a Malaysian tertiary institution undertaking an Australian course and considers the extent to which these elements are viewed differently. Findings indicate that both groups deem high quality students and international accreditation as crucial aspects of internationalisation expectations.